Immobilization of CGTase from Bacillus licheniformis on pineapple waste for production of cyclodextrin - Rohaida, Che Man; Rosnida, Ab Rahim (2021)
CD is a nonreducing maltooligosaccharides with a hydrophobic inside and hydrophilic surface outside. CD able to form inclusion complexes with many hydrophobic molecules, changing their physical and chemical properties. Ability to reduce of unwanted taste and odour in food and pharmaceutical. CD also approved by Generally Recognized As Safe (GRAS) and Food and Drug Administration (FDA) in food application.